Arranjo institucional do financiamento do ensino fundamental no Brasil: considerações sobre os municípios brasileiros e estudo de caso do município de São Paulo no período de 1997 a 2006 - Peres, Ursula Dias (2007)
The institutional environment of elementary education funding in Brazil suffered several modifications in the last decades, mainly during the 1990's. In order to join the prioritization of elementary education to the decentralization of educational public policies – leading it to local level – the federal government promoted a deep reform in the legal framework, even through constitutional amendments that became important rules for education funding. One of the major changes was the creation of the 'Elementary Education Development and Maintenance and Teachers Valorization Fund' (Fundo de Manutenção e Desenvolvimento do Ensino Fundamental e Valorização do Magistério – FUNDEF) destined to the financing of elementary education in Brazil. Despite these reforms, the situation of elementary education in Brazil is still extremely precarious: neither does it fulfills the needs of its people, nor is compatible with Brazilian State economical capacities. From the analytical standpoint, with basis on the 'New Institutional Economy' theoretical reference, the creation of earmarked revenues for education policies is considered the main financing rule for elementary education, and served to reduce several transaction costs. These costs are associated to the discontinuity of actions and to the opportunistic behavior of the players involved in the public policies’ scenario. Among these players are representatives of the executive, legislative and public powers, state bureaucracy and civil society. This thesis seeks to evaluate if this set of education financing strategies - created by earmarked revenues mainly for elementary education - is sufficient condition to achieve the efficiency required to carry out those education policies, or if other effects, linked to the strategy or not, contribute to the maintenance of inefficiencies. This thesis uses as theoretical reference the 'New Institutional Economy', which is mainly based in the works by North (1988 and 1990), Williamson (1985) and Miller (1992). This reference focuses on the central role of institutions in the evaluation of social-economical problems. Thus, the first session of the thesis aims at describing the core elements of this theory, such as the concepts of formal and informal rules, transaction costs and governance structures. Based on this initial structure, the theoretical model used in the thesis is built and can be considered as an adaptation of the New Institution Economy approach for organizations in the public sector. This model takes into consideration important elements and characteristics of institutions, players and governance structures that should be accounted for when analyzing public organizations. Under the light of this theoretical model, the institutional array developed for elementary education financing in Brazilian cities is analyzed into further detail; comprehending the institutional scenario, that is, the rules of the game, and the behavior of the players face to these rules. In order to empirically test the theoretical assumptions of this thesis, a case study is carried out in the city of São Paulo. The present thesis aims at contributing to the discussions on the necessary changes on education policies, with special emphasis in the institutional adequacy between the formal rules established to the policies and the characteristics, values and skills of the players involved in the implementation of these rules. The very institutional theory anticipates that the disregard of these factors implies the possibility of occurring transaction costs associated to public manager control costs and to the opportunistic behavior of the players involved in the public policies’ scenario. Therefore, even in the existence of earmarked revenues, the efficient conduction of public education policies will not be guarantied.